2005
DOI: 10.1002/ijc.21542
|View full text |Cite
|
Sign up to set email alerts
|

Hamartin and tuberin: Working together for tumour suppression

Abstract: TSC1 and TSC2 are two recently identified tumour suppressor genes encoding hamartin and tuberin, respectively, and involved in pathogenesis of tuberous sclerosis, neurological disorder connected with the development of hamartomas in numerous organ systems, including the brain, kidneys, heart and liver. Both protein products of TSC1 and TSC2 form an intracellular complex exerting GTPase-activating (GAP) activity towards a small G protein, Ras homologue enriched in brain (Rheb). Inhibition of Rheb is important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 40 publications
0
44
0
4
Order By: Relevance
“…Therefore, the precise role of IGF1R and PDGFR-b in schwannoma development needs further clarification. Jozwiak, 2006). Hence, the role of these proteins in vesicular trafficking could be key to their tumor suppressing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the precise role of IGF1R and PDGFR-b in schwannoma development needs further clarification. Jozwiak, 2006). Hence, the role of these proteins in vesicular trafficking could be key to their tumor suppressing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of TSC2 influences its activity within the complex with TSC1. At least three kinases, Akt, RSK1 and MAPK, are involved in TSC2 phosphorylation (Jozwiak, 2006). Several studies reported that HPV proteins target the components of PI3 kinase and Akt-mediated cell growth pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Первым компонентом СПМТ является TSC (tuberous sclerosis complex), который со-стоит из двух взаимодействующих белков, образующих гетеродимерный комплекс [2][3][4]. Один из этих белков -TSC2 (или ту-берин) -функционирует как специфическая гуанозинтрифосфатаза (ГТФаза), активиру-ющая белок (GAP), который ингибирует Rheb (член суперсемейства малых ГТФ-свя-зывающих белков Ras).…”
Section: компоненты сигнального пу ти Mtor и их функцииunclassified